Мейотична мутація томату, що порушує конденсацію хроматину - Лісовська, Т.П.; Кузьмішина, І.І.; Коцун, Л.О.; Войтюк, В.П.; Андреєва, В.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. This paper presents the results of cytological and genetic analysis of new meiotic mutant of tomato (Lycopersicon esculentum Mill.) sti. Methods. Studies on meiosis in microsporogenesis were made in iron-acetocarmine smears of anther fixed in acetic alcohol (3:1). Results. Cytological analysis revealed that starting from the stage dyplotene and diakinesis chromosomes showed defects in condensation by fuzzy contours, irregular chromosomes condensation, intertwined chromatin, non-homologous chromosomes and univalents that are difficult to identification. Meiotic mutation tomato sti (stickyness) is monogenic recessive nature of inheritance. Mutant plants exhibit a high male and female sterility. Conclusions. Meiotic mutant of tomato sti is defected in chromosome condensation.